Peningkatan Pendidikan Berbasis Kearifan Lokal Melalui Media Wayang Kulit Sejak Usia Dini - Nur Hasanah, Eli; Hidayatu Munawaroh (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Early childhood education is very fundamental education in providing the basic framework for the formation of subsequent knowledge, attitudes and skills. This research uses a qualitative approach with descriptive research type. This research aims to provide a deep and meaningful learning experience, as well as enrich children's understanding of Indonesia's cultural heritage. Through this approach, it is hoped that a sense of love and pride in local wisdom can grow, foster positive character, and build a solid foundation for children's intellectual and moral development.